2021
DOI: 10.3389/fonc.2020.594366
|View full text |Cite
|
Sign up to set email alerts
|

A Correlative Study Between IVIM-DWI Parameters and the Expression Levels of Ang-2 and TKT in Hepatocellular Carcinoma

Abstract: BackgroundNoninvasive evaluation of the expression of angiopoietin-2 (Ang-2) and transketolase (TKT) in hepatocellular carcinoma (HCC) is of great significance for the clinical development of individualized treatment plans. However, the correlation between intravoxel incoherent motion diffusion weighted imaging (IVIM-DWI) and the expression of Ang-2 and TKT has not been reported. We sought to investigate the correlations between IVIM-DWI parameters and Ang-2 and TKT expression levels in HCCs.MethodsConventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Although promising results were observed in healthy volunteers, the proposed optimal 2D sampling also needs to be rigorously validated in the relevant patient populations. [5][6][7][8][9][10][11][12][13][14][15] In conclusion, 2D b-M 1 -optimized data acquisition enables repeatable IVIM quantification with improved noise performance in healthy volunteers. Therefore, this work may advance the establishment of IVIM-based quantitative biomarkers for the detection and staging of chronic and focal liver diseases.…”
Section: F I G U R Ementioning
confidence: 79%
See 1 more Smart Citation
“…Although promising results were observed in healthy volunteers, the proposed optimal 2D sampling also needs to be rigorously validated in the relevant patient populations. [5][6][7][8][9][10][11][12][13][14][15] In conclusion, 2D b-M 1 -optimized data acquisition enables repeatable IVIM quantification with improved noise performance in healthy volunteers. Therefore, this work may advance the establishment of IVIM-based quantitative biomarkers for the detection and staging of chronic and focal liver diseases.…”
Section: F I G U R Ementioning
confidence: 79%
“…Intravoxel incoherent motion (IVIM) DWI is an MR‐based technique capable of quantifying parameters related to the microstructure of liver tissue, including measures of diffusivity (diffusion coefficient ( D )) and microcirculation of blood (perfusion fraction ( F) and blood velocity SD ( V b , which is related to the pseudo‐diffusion parameter D* )) 3,4 . Several studies have demonstrated the potential utility of quantitative IVIM‐DWI in the evaluation of liver diseases, including fibrosis, 5–7 hepatitis, 8 fatty liver disease, 9,10 hepatocellular carcinoma, 5,11–13 and metastatic lesions 14,15 . However, the predictive performance (e.g., distinguishing benign vs. malignant or responding vs. nonresponding) of the blood microcirculation or perfusion parameters suffers from high measurement variability and poor precision (repeatability and reproducibility) when using conventional IVIM‐DWI methods 5,6,11,15–18 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the CD34 was used to label ECC blood vessels to count MVD, because its specificity for vascular endothelium is much higher than other markers. The number of tumor neovascularization can be intuitively determined by counting MVD, so as to determine the tumor tissue malignant degree [ 35 ]. VEGF is a polypeptide factor that can specifically induce the new blood vessels formation in tumor tissues and usually acts on tumor vascular endothelial cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, liposomes give the opportunity to deliver both hydrophobic and hydrophilic compounds, but also genetic material. In MPM treatment, liposomes are exploited to deliver chemotherapeutics, such as doxorubicin [54,55], or pemetrexed [56,57], with the main goal to increase the concentration of drugs in the peritoneal cavity, to avoid fast degradation of drug molecules, and to have the possibility Comparing the two images, it can be observed that even if the CT/PET scan allows a greater morphological detail, the IVIM sequence has an equal capacity to highlight, with hyper-intensity of the signal, the same functional aspects.…”
Section: Nanoparticles (Nps) As Novel Promise For Mpmmentioning
confidence: 99%
“…Moreover, liposomes give the opportunity to deliver both hydrophobic and hydrophilic compounds, but also genetic material. In MPM treatment, liposomes are exploited to deliver chemotherapeutics, such as doxorubicin [54,55], or pemetrexed [56,57], with the main goal to increase the concentration of drugs in the peritoneal cavity, to avoid fast degradation of drug molecules, and to have the possibility to prolong the release of the drug. For example, Ando et al demonstrated that an injection into the pleural cavity of pemetrexed loaded into liposomes had more suppressive effect on tumor growth in an orthotopic mesothelioma mouse model, compared to free pemetrexed.…”
Section: Nanoparticles (Nps) As Novel Promise For Mpmmentioning
confidence: 99%